Differences in the Effectiveness of Boiled Water for Binahong Leaves and Boiled Water for Betel Leaves on Healing Perineal Rupture in Maternal Maternity at Saketi Public Health Center, Pandeglang Regency in 2022 - Lili Farlikhatun; Devi Pitriyani (STIKep PPNI Jawa Barat, 2023)
Aims: The purpose of this study was to determine the boiled water of binahong leaves and boiled water of betel leaf on the healing of a perineal rupture in women giving birth at Saketi Public Health Center, Pandeglang Regency Methods: This study uses a quasi-experimental approach through two groups with a control post-test design where the sample is taken using total sampling divided into 2 treatment groups. Results: The results of the study were based on age, most of the respondents were 7 (21.9%) aged 26-30 years. Based on the level of education, it can be seen that most of the respondents as many as 18 (56.3%) have a junior high school education level and Based on parity most of the respondents as many as 19 (59.4%) are multipara. The average healing time of perineal rupture in the control post-test group was 7 days and the average perineal rupture healing time in the intervention post-test group was 5 days, there was a difference in the effectiveness of binahong leaf boiled water and betel leaf boiled water with (p-value 0.000 < (0.05)) Conclusion: Showed that there was a difference in the effectiveness of binahong leaf boiled water and betel leaf boiled water with (p-value 0.000 < (0.05)).